The maize fused leaves1 (fdl1) gene controls organ separation in the embryo and seedling shoot and promotes coleoptile opening - La Rocca, Nicoletta (J Exp Bot, 2015)
The fdl1-1 mutation, caused by an Enhancer/Suppressor mutator (En/Spm) element insertion located in the third exon of the gene, identifies a novel gene encoding ZmMYB94, a transcription factor of the R2R3-MYB subfamily. The fdl1 gene was isolated through co-segregation analysis, whereas proof of gene identity was obtained using an RNAi strategy that conferred less severe, but clearly recognizable specific mutant traits on seedlings. Fdl1 is involved in the regulation of cuticle deposition in young seedlings as well as in the establishment of a regular pattern of epicuticular wax deposition on the epidermis of young leaves. Lack of Fdl1 action also correlates with developmental defects, such as delayed germination and seedling growth, abnormal coleoptile opening and presence of curly leaves showing areas of fusion between the coleoptile and the first leaf or between the first and the second leaf. The expression profile of ZmMYB94 mRNA—determined by quantitative RT-PCR—overlaps the pattern of mutant phenotypic expression and is confined to a narrow developmental window. High expression was observed in the embryo, in the seedling coleoptile and in the first two leaves, whereas RNA level, as well as phenotypic defects, decreases at the third leaf stage. Interestingly several of the Arabidopsis MYB genes most closely related to ZmMYB94 are also involved in the activation of cuticular wax biosynthesis, suggesting deep conservation of regulatory processes related to cuticular wax deposition between monocots and dicots.